2024
DOI: 10.1186/s12964-023-01402-y
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of α-synucleinopathy in the disruption of microglial homeostasis contributes to the pathogenesis of Parkinson’s disease

Yongzhen Miao,
Hongrui Meng

Abstract: The intracellular deposition and intercellular transmission of α-synuclein (α-syn) are shared pathological characteristics among neurodegenerative disorders collectively known as α-synucleinopathies, including Parkinson's disease (PD). Although the precise triggers of α-synucleinopathies remain unclear, recent findings indicate that disruption of microglial homeostasis contributes to the pathogenesis of PD. Microglia play a crucial role in maintaining optimal neuronal function by ensuring a homeostatic environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 235 publications
0
11
0
Order By: Relevance
“…Overall, it may be concluded that microglia play a pivotal role in the spread of α-Syn and the eventual pathophysiology of synucleinopathies, including those related to circadian rhythm dysfunction. Therefore, extensive effort is expended in elucidating the molecular mechanism(s) of microglial interactions with α-Syn in the hope of identifying novel therapeutic targets for prominent neurodegenerative diseases, including PD [85,86]. It is also worth mentioning that TLR 4 is required for the α-Syn-dependent activation of microglia [92,93] Very recently, however, it was discovered that the α-Syn structure changes when it is phosphorylated.…”
Section: Microglia Synucleinopathiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, it may be concluded that microglia play a pivotal role in the spread of α-Syn and the eventual pathophysiology of synucleinopathies, including those related to circadian rhythm dysfunction. Therefore, extensive effort is expended in elucidating the molecular mechanism(s) of microglial interactions with α-Syn in the hope of identifying novel therapeutic targets for prominent neurodegenerative diseases, including PD [85,86]. It is also worth mentioning that TLR 4 is required for the α-Syn-dependent activation of microglia [92,93] Very recently, however, it was discovered that the α-Syn structure changes when it is phosphorylated.…”
Section: Microglia Synucleinopathiesmentioning
confidence: 99%
“…Although the etiology of synucleinopathies remains unknown, microglia were directly implicated in its pathogenesis. It is worth reiterating that microglia offer neuroprotection in the early stages of α-Syn accumulation; however, in chronic disease conditions, structural variations may accompany inherited faulty α-Syn, resulting in distorted microglial receptor interactions [ 85 , 86 ]. Thus, while microglial receptors initially enable cellular recognition and the uptake of α-Syn, in chronic disease states, the physiological functions of microglia are overwhelmed.…”
Section: Microglia Synucleinopathiesmentioning
confidence: 99%
See 3 more Smart Citations